Islam Agama Dakwah - Fahmi Rusydi (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
. Islam is a religion of grace that invites people to leave the act of kufr and called towards monotheism which is full of goodness values ??in it. A belief (faith) in Allah which was engraved in a person must realize the internalization of Qur'an. The value impact of faith should have a great influence interms of a devout man, pious and noble. The impact can improve the spiritual, personal hygiene and care and compliance of a Muslim every day and this effect does not make the material power and lust as the goal but it should obedience and submission to the Creator (al-Khaliq). Moreover, Islam is a da’wah religion that has a unique, both past and present, that is easily spread this teachings to the world, and the number of people entered into Islam. This is because Islamic teachings is in accordance with the nature and the human mind, full of tolerance, easy to practice as well.